"The Tools of Your Chants and Spells": Stories of Madwomen and Indian Practical Healing. Issue 3 (3rd May 2016) - Pinto, Sarah
ABSTRACT: A longstanding trope in Indian psychiatry, and in popular representations of it, involves the efficacy of incantations and exorcism in healing afflictions of the mind, notably hysteria. In many accounts, from nineteenth century medical journals to twenty-first century popular films, a medicine deemed at once 'Western' and universal is granted the ability to diagnose neurotic afflictions, but rendered incapable of curing them, while bodily techniques referred to as 'Indian' are granted efficacy. In this article, I explore the subtleties and implications of this recurrent knowledge paradigm. I argue that a particular arrangement—one in which difference is established through equivalence—undergirds the terms by which medicine comes to be viewed as a cultural encounter. As these progressive formulations are often founded on stories about women's madness, I ask, what are the implications of an arguably pragmatic ethos founded on an uneven—and deeply gendered—resolution to postcolonial knowledge problems?